2023
DOI: 10.1101/2023.02.14.528567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prdm16 and Vcam1 regulate the postnatal disappearance of embryonic radial glia and the ending of cortical neurogenesis

Abstract: Embryonic neural stem cells (NSCs, i.e., radial glia) in the ventricular-subventricular zone (V-SVZ) generate the majority of neurons and glia in the forebrain. Postnatally, embryonic radial glia disappear and a subpopulation of radial glia transition into adult NSCs. As this transition occurs, widespread neurogenesis in brain regions such as the cerebral cortex ends. The mechanisms that regulate the postnatal disappearance of radial glia and the ending of embryonic neurogenesis remain poorly understood. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(141 reference statements)
2
2
0
Order By: Relevance
“…Histological and transcriptomic analysis of human organoids suggests a PRDM16 control of various aspects of neural stem cell biology including progenitor proliferation, transition of apical PAX6 + RG progression to basal HOPX + RG, aspects of cell adhesion, and migration. This is consistent with previous findings in mice showing that PRDM16 promotes cortical RG lineage progression into ependymal cells or adult neural stem cells [ 15 , 16 ]. Future experiments with more sophisticated human organoids systems that allow the study of PRDM16’s role in the generation of basal RG, neuronal migration that ultimately contribute to the expansion of the human brain will be necessary for addressing this question.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Histological and transcriptomic analysis of human organoids suggests a PRDM16 control of various aspects of neural stem cell biology including progenitor proliferation, transition of apical PAX6 + RG progression to basal HOPX + RG, aspects of cell adhesion, and migration. This is consistent with previous findings in mice showing that PRDM16 promotes cortical RG lineage progression into ependymal cells or adult neural stem cells [ 15 , 16 ]. Future experiments with more sophisticated human organoids systems that allow the study of PRDM16’s role in the generation of basal RG, neuronal migration that ultimately contribute to the expansion of the human brain will be necessary for addressing this question.…”
Section: Discussionsupporting
confidence: 93%
“…Our organoid data are consistent with previous findings that, in the embryonic mouse cortex, the absence of Prdm16 decreases the number and cycling of Eomes progenitors and increases cell cycle exit. It is also consistent with a recent paper suggesting that the absence of Prdm16 leads to the persistence of RG into late postnatal stages [ 16 ]. The increase was observed only in apical progenitors but not in the basal progenitors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, Dlx1, another highly active InN2 regulon that plays a role in regulating the functional longevity of GABAergic interneurons in the hippocampus, regulates Prdm16 and drives the expression of Prdm16-regulated Meis2 gene. Interestingly, a recent study also indicated that high Prdm16 expression is essential in promoting the disappearance of radial glia and the ending of cortical neurogenesis in the postnatal mouse brain [131]. Collectively, these findings, supported by the existing literature, allowed us to hypothesize that InN2 cells characterized by high Prdm16 expression could represent a specific developmental stage during adult neurogenesis captured only in cells from sedentary mice, possibly as a result of faster maturation of these Prdm16-high neurons upon exercise.…”
Section: Discussionsupporting
confidence: 70%